THE EFFECT OF MOTIVATION, CREATIVITY AND BUSINESS LOCATION ON THE SUCCESS OF MICRO, SMALL AND MEDIUM ENTERPRISES (MSMEs) IN THE AHAD MARKET OF CULINARY TOURISM IN LHOKSEUMAWE CITY - Mhd Aldiani; Munandar; M.Subhan; Agustinawati (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze the influence of motivation, creativity, and business location on the success of micro, small, and medium enterprises (MSMEs) at the Ahad Culinary Tourism Market in Lhokseumawe City. The research method used is a quantitative approach, with data collected through questionnaires distributed to 90 MSME respondents. The data were analyzed using multiple linear regression analysis. The results of the study indicate that: (1) Motivation has a positive and significant influence on the success of MSMEs. The higher the motivation of business actors, the greater their chances of achieving success in facing business challenges. (2) Creativity also has a positive and significant influence on the success of MSMEs. This highlights the importance of supporting creativity development through training or facilitation by local governments and business communities. (3) Business location has a positive and significant influence on the success of MSMEs. A strategic business location has been proven to support increased sales and improve consumer access to the products or services offered.